Polyfunctional Coatings on the Basis of Powder Paints Electrostatically Sprayed from the Composite Mixtures Treated in Planetary Ball Mill; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Panin S. V. Sergey Viktorovich; Yazykov S. Y. Sergei; Kornienko L. A. Larisa; Ovechkin B. B. Boris Borisovich (Design of Multiscale Composites and Polymers of New Generation, 2016)
Title screen